2015
DOI: 10.18632/oncotarget.3560
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiling identifies MiR-195 suppresses osteosarcoma cell metastasis by targeting CCND1

Abstract: Metastasis is a leading cause of mortality for osteosarcoma patients. The molecular pathological mechanism remains to be elucidated. In the previously study, we established two osteosarcoma cell lines with different metastatic potentials. Differential expressed genes and proteins regarding metastatic ability have been identified. MicroRNAs are important regulators in tumorigenesis and tumor progression. In this study, microRNA microarray was used to assess the differential expressed miRNAs level between these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 32 publications
(39 reference statements)
3
72
0
2
Order By: Relevance
“…Recent studies showed that miRNAs play vital roles in regulating individual development, cell proliferation, metabolism, differentiation, invasion and migration in different disease [16-22]. A number of studies dispalyed that different miRNAs could increase or decrease cell apoptosis in OA, such as miR-149 and miR-30b [23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that miRNAs play vital roles in regulating individual development, cell proliferation, metabolism, differentiation, invasion and migration in different disease [16-22]. A number of studies dispalyed that different miRNAs could increase or decrease cell apoptosis in OA, such as miR-149 and miR-30b [23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sun et al 26 reported that miR-195 was down-regulated in esophageal squamous cell carcinoma and negatively correlates with advanced clinical stage and lymphatic metastasis. Han et al 27 showed that in osteosarcoma, miR-195 was significantly down-regulated in highly metastatic osteosarcoma cell line and inhibited the invasion and migration of osteosarcoma cells via targeting CCND1. Yang et al 28 showed that miR-195 can inhibit the invasion and metastasis by inhibiting the expression of Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recent advances in the treatment of osteosarcoma such as radiation therapy, adjuvant chemotherapy and surgery that have been achieved, the relative 5-year survival rate of osteosarcoma patients remains discontent [6][7][8][9][10]. Although various studies have investigated the development and mechanism of osteosarcoma, the molecular mechanism of osteosarcoma is still elusive [11][12][13]. Therefore, it is urgent to find novel therapeutic approaches and targets for treating osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%